2011
DOI: 10.1021/jm200278m
|View full text |Cite
|
Sign up to set email alerts
|

New, Potent, Selective, and Short-Acting Peptidic V1a Receptor Agonists

Abstract: [Arg(8)]vasopressin (AVP) produces vasoconstriction via V(1a) receptor (V(1a)R)-mediated vascular smooth muscle cell contraction and is being used to increase blood pressure in septic shock, a form of vasodilatory hypotension. However, AVP also induces V(2) receptor (V(2)R)-mediated antidiuresis, vasodilation, and coagulation factor release, all deleterious in septic shock. The V(1a)R agonist terlipressin (H-Gly(3)[Lys(8)]VP) also lacks selectivity vs the V(2)R and has sizably longer duration of action than AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…The maximum dose was based on a study of Torgersen et al (47) who reported the safety of AVP doses up to 0.067 units/min in patients with septic shock. Because POV has a similar potency (EC 50 ) as AVP at the human V 1a receptor (28,54), infusion preparations had the same concentrations. However, the selectivity of POV for the V 1a -versus the V 2 receptor is more than 220 times higher than AVP, thus resulting in a lack of V 2 -receptor activity (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum dose was based on a study of Torgersen et al (47) who reported the safety of AVP doses up to 0.067 units/min in patients with septic shock. Because POV has a similar potency (EC 50 ) as AVP at the human V 1a receptor (28,54), infusion preparations had the same concentrations. However, the selectivity of POV for the V 1a -versus the V 2 receptor is more than 220 times higher than AVP, thus resulting in a lack of V 2 -receptor activity (2).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation is the lack of dose response studies in the present sepsis model. However, appropriate pharmacological studies with POV and AVP have been published recently (54).…”
Section: Discussionmentioning
confidence: 99%
“…1 was particularly selective vs. the V1aR (>1000-fold) presumably due to the desamino modification [6]. The Val 4 analogue of 1 ([Val 4 ]dDAVP, 2) has been reported to be more potent and selective than 1 in rat in vivo models [7].…”
Section: Resultsmentioning
confidence: 99%
“…158 The treatment of vasodilatory hypotension as observed in septic shock would however require a V 1a R-selective agonist with a short half-life. 159 The synthesis of analogs of AVP modified in positions 2, 3, 4, and 8 afforded a series of compounds with a suitable profile, among them 80 (FE202158, Figure 8.29), 158 which was found to be a potent and selective full agonist at the human V 1a receptor (Table 8.5) and also a potent vasoconstrictor in vivo in rats, as shown by dose-dependent reduction of ear skin blood flow (ED 50 of 4.0 pmol kg À1 min À1 ; given by constant intravenous infusion), with no V 2 R mediated antidiuretic activity. 159 Macrocycle 80 (FE202158) was chosen for clinical trials for the treatment of septic shock.…”
Section: Vasopressin Receptor (V 1a ) Agonists: Fe202158mentioning
confidence: 99%